Razlike v visini in kontaktnem casu razlicnih skokov treh osnovnih tipov mladih kosrkarjev - Erculj, F.; Dezman, B.; Vuckovic, G. (Kinesiologia Slovenica, 2004)
The aim of this study was to establish whether there were any differences in various types of jumps between three types of young basketball players, namely in terms of two- and one-leg jumps which are the most frequent type of jumps in basketball. For this purpose we sampled 50 male basketball players, aged 16 and 17, who were the top basketball players of their age group in Slovenia. The sample was further divided into three subsamples: guards (n=18), forwards (n=18) and centres (n=14). Based on the results of the analysis of variance and the discriminant analysis it may be concluded that individual types of players differ greatly in terms of results of all five tests (jumps). In all five tests the best results (height or length of jump) were achieved by guards, followed by forwards and centres. In terms of contact time (duration of take-off) the differences between the three types of players were not so obvious and were statistically significant only in two cases.